The positive impact of physical activity on academic performance among catalan adolescents - E. Roig-Hierro; X. Ríos-Sisó; F. Buscà; M. Guillem; A. Batalla (Cogent Education)
Physical activity (PA) positively influences academic performance, yet the specific effects of PA frequency and intensity remain underexplored. This study examines the association between weekly PA frequency and intensity and academic outcomes among 1,524 adolescents in Catalonia, using data from the latest PISA assessment. Academic performance in mathematics, science, and language, along with perceived competence in related tasks, was analyzed using a cross-sectional design. Chi-square tests and Spearman’s correlations were conducted. Results indicate that moderate PA (2–5 times per week) is linked to higher academic performance across all subjects, while excessive PA (more than five times weekly) is associated with decreased performance, possibly due to reduced academic focus. Gender moderated the relationship in the language domain but not in mathematics or science. PA also positively influenced perceived competence in teamwork and problem-solving, suggesting broader developmental benefits. These findings emphasize the importance of balancing PA to optimize cognitive and psychosocial outcomes. Integrating structured, moderate PA into school curricula may enhance both academic performance and life skills. Tailored interventions that account for gender and fitness levels could further improve outcomes. Future research should explore longitudinal effects and specific PA characteristics to inform educational strategies..